Metacognitive reading strategies awareness and metacognitive reading strategies use of EFL university students across gender - Zhenita Deliany; Bambang Yudi Cahyono (Universitas Syiah Kuala, 2020)
This study investigates EFL students’ metacognitive reading strategies awareness and their metacognitive reading strategies use. It also compares female and male EFL students in terms of their metacognitive reading strategies awareness and metacognitive reading strategies use. The quantitative research method is used through the survey research design. The study involves 53 undergraduate students, consisting of 33 females and 20 males. The data are collected by using a questionnaire of Metacognitive Awareness of Reading Strategy Inventory (MARSI-R inventory) developed by Mokhtari et al. (2018). The strategies on the MARSI-R inventory were scored on 1-5 scales. The data were analyzed through a simple calculation to find out the level of awareness of the students, and the statistical test of independent sample t-test were conducted to know the difference between females and males. The results show that all of the students possess high metacognitive reading strategies awareness, indicating high metacognitive reading strategies use. Despite there is a different level of awareness between female and male students, further analysis using an independent sample t-test shows that the level of awareness between the two is .742 (p0.05), meaning that the difference is not significant. The result of the research also shows that there are no significant differences in all subscales of metacognitive reading strategies use across gender. The p-value for global reading strategies is .224, for problem-solving strategies is .486, and for support reading strategies is .249. Thus, gender plays no role in determining the metacognitive reading strategies awareness and metacognitive reading strategies use.